2013
DOI: 10.1111/bdi.12105
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of restarted lithium treatment after discontinuation: reviewing the evidence for discontinuation‐induced refractoriness

Abstract: Although studies are scarce, review and meta-analysis of the available literature does not provide convincing evidence that lithium is less effective when treatment is discontinued and restarted, compared to uninterrupted treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
1
11
0
2
Order By: Relevance
“…However, the assumption for the existence of lithium-discontinuation-related refractoriness is not supported by studies reporting that even when samples enriched for lithium refractoriness were used, no inferiority of lithium to the other agent was documented (Bowden et al, 1994). Also a recent meta-analysis of all published cases concluded that there is not sufficient data to support such a concept (de Vries et al, 2013). …”
Section: Efficacy Datamentioning
confidence: 99%
“…However, the assumption for the existence of lithium-discontinuation-related refractoriness is not supported by studies reporting that even when samples enriched for lithium refractoriness were used, no inferiority of lithium to the other agent was documented (Bowden et al, 1994). Also a recent meta-analysis of all published cases concluded that there is not sufficient data to support such a concept (de Vries et al, 2013). …”
Section: Efficacy Datamentioning
confidence: 99%
“…Konklusiv auch zu diesen neuen "real world" Studienergebnissen empfiehlt die NICE-Leitlinie (National Institute for Health and Care Excellence) Patienten nach Abschluss einer Akutbehandlung mit einer anderen Substanz als Lithium darüber aufzuklären, dass Lithium die effektivste Phasenprophylaxe darstellt und zu besprechen, ob die Fortsetzung der bisherigen Behandlung oder der Wechsel zu Lithium gewünscht wird [5]. Darüber hinaus scheint Lithium entgegen früherer Befürchtungen weder im Langzeitverlauf (prospektive Nachuntersuchung bis zu 20 Jahre, im Mittel 10 Jahre) [19] noch nach Wiederaufnahme einer Lithiumbehandlung an Effektivität einzubüßen [20].…”
Section: Phasenprophylaxeunclassified
“…Neither, conclusive evidence exists about the actual occurrence of loss of lithium prophylaxis and/or enduring response over the time [ 9 , 19 ].…”
Section: Introductionmentioning
confidence: 99%